Regulating two-sided markets: an empirical investigation - Santiago Carbó-Valverde; Sujit Chakravorti; Francisco Rodríguez Fernández (European Central Bank (ECB), 2009)
We study the effect of government encouraged or mandated interchange fee ceilings on consumer and merchant adoption and usage of payment cards in an economy where card acceptance is far from complete. We believe that we are the first to use bank-level data to study the impact of interchange fee regulation. We find that consumer and merchant welfare improved because of increased consumer and merchant adoption leading to greater usage of payment cards. We also find that bank revenues increased when interchange fees were reduced although these results are critically dependent on merchant acceptance being far from complete at the beginning and during the implementation of interchange fee ceilings. In addition, there is most likely a threshold interchange fee below which social welfare decreases although our data currently does not allow us to quantify it.
Keywords: L11; G21; D53; 330; consumer payment choice; merchant payment adoption; network competition; Kreditkarte; Bankentgelt; Anreizregulierung; Konsumentenverhalten; Netzwerkökonomik; Soziale Wohlfahrtsfunktion; Spanien